(untitled) (Revista INTEREDU11, 2024)
The aim of this essay is to highlight the importance of promoting intercultural coexistence in schools, from primary to higher education. For this purpose, scientific literature has been searched and a reflection has been carried out on the data found in relation to the increasingly latent intercultural nature in educational centres. It is concluded that differential pedagogy is necessary for its relevant role in the achievement of social justice and equity in education. Bullying and cyberbullying are part of the daily reality of migrant and refugee students in schools, a situation that must be ended by promoting social awareness through creative projects and ideas. Collaboration with associations of migrants and their families should be encouraged. Actions and workshops are proposed to teachers to help them improve the classroom climate for the development of this new and necessary social awareness.